Students’ Academic Adjustment Viewed From Peer Interpersonal Communication - Hendriani, Awaliyah Putri; Saud, Habel; Mataputun, Yulius; Reba, Yansen Alberth; Muttaqin, M. Zaenul; Karisma, Sally Putri; Putra, Miftah Fariz Prima (LP4MK STKIP PGRI Lubuklinggau, 2025)
This study investigates the influence of peer interpersonal communication on academic adjustment among students of the Guidance and Counseling Study Program at Cenderawasih University. Using a quantitative associative design, data were collected from 102 students through total sampling and analyzed using simple linear regression. The results revealed a significant and positive relationship between peer communication and academic adjustment (t = 10.717, p < 0.05), with a correlation coefficient of R = 0.788 and R² = 0.621. These findings indicate that 62.1% of students’ academic adjustment can be explained by their level of interpersonal communication with peers. Students who demonstrate higher communication skills tend to adapt better academically, showing improved emotional stability, motivation, and collaboration. Theoretically, this study supports Devito’s interpersonal communication framework and Bandura’s Social Learning Theory, highlighting communication as a crucial factor in adaptive learning. Practically, the findings emphasize the need for universities to strengthen peer-based mentoring and communication training programs to enhance students’ academic resilience and success in higher education.